Checkpoint-inhibitor induced Polyserositis with Edema - Zierold, Sarah; Akcetin, Larissa Semra; Gresser, Eva; Maier, Anna Marie; Koenig, Alexander; Kramer, Rafaela; Theurich, Sebastian; Tomsitz, Dirk; Erdmann, Michael; French, Lars E.; Rudelius, Martina; Heinzerling, Lucie (Cancer Immunology, Immunotherapy, 2022)
Background As immune checkpoint inhibitors (ICI) are increasingly being used due to effectiveness in various tumor entities, rare side effects occur more frequently. Pericardial effusion has been reported in patients with advanced non-small cell lung cancer (NSCLC) after or under treatment with immune checkpoint inhibitors. However, knowledge about serositis and edemas induced by checkpoint inhibitors in other tumor entities is scarce. Methods and results Four cases with sudden onset of checkpoint inhibitor induced serositis (irSerositis) are presented including one patient with metastatic cervical cancer, two with metastatic melanoma and one with non-small cell lung cancer (NSCLC). In all cases treatment with steroids was successful in the beginning, but did not lead to complete recovery of the patients. All patients required multiple punctures. Three of the patients presented with additional peripheral edema; in one patient only the lower extremities were affected, whereas the entire body, even face and eyelids were involved in the other patients. In all patients serositis was accompanied by other immune-related adverse events (irAEs). Conclusion ICI-induced serositis and effusions are complex to diagnose and treat and might be underdiagnosed. For differentiation from malignant serositis pathology of the punctured fluid can be helpful (lymphocytes vs. malignant cells). Identifying irSerositis as early as possible is essential since steroids can improve symptoms.
CRIS-Team WoS Importer:2022-06-03
Keywords: Autoimmunity; Anti-PD1-antibody; Side effects; Serositis; Pericardial effusion; Pleural effusion